«Det var den sjansen vi hadde» - Om rituelle avskjedsmarkeringar for barn som døyr før dei blir fødde (Tidsskrift for Praktisk Teologi, 2023)
En engelsk oversettelse av artikkelen er publisert på samme side.How to bid farewell to a child never known? In this article I discuss challenges connected to ritual farewell events for the stillborn. Stillborn children have been excluded from traditional funerals and burials in many cultures. Until a few decades ago, this was also the case in Norway. The Norwegian Church has now stated the right for everyone to have their own grave, and chaplains assist bereaved parents in farewell ceremonies. Based on interview material with bereaved parents and participant observation from farewell events, this article seeks to highlight the question of ritual farewells from bereaved parents’ point of view. The need for individual adjustment stands out as a compelling concern. Parents underlined the importance of their own preferences being heeded to, but also the need for information about actual possibilities. The availability of proficient counselling, open to the complexity of the issue involved, was found to be crucial.